2013
DOI: 10.1095/biolreprod.112.103168
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Circulating DNA Distribution in Pregnant and Nonpregnant Dairy Cows1

Abstract: Circulating nucleic acids (CNAs) are free-floating, cell-free DNA and RNA molecules in the circulation of healthy and diseased humans and animals. The aim of this study was to identify differences in CNA distribution in serum samples from multiparous pregnant (n = 24) and nonpregnant (n = 16) dairy cows at different days of gestation (Days 0, 20, and 40). A modified serial analysis of gene expression procedure was used to generate concatemerized short sequence tags from isolated serum DNA. A total of 6.1 × 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…In addition, the diagnostic utility of CNAs has been shown in cattle and elk with bovine spongiform encephalopathy (Gordon et al, 2009). The analysis of cfDNA in domestic animals has been reported in several studies demonstrating cfDNA as useful markers in diagnosis (Beck et al, 2009(Beck et al, , 2013Brenig, Schütz & Urnovitz, 2002;Gordon et al, 2009;Mayer et al, 2013aMayer et al, , 2013bSchütz et al, 2005).…”
Section: Analysis Of Cell-free Circulating Nucleic Acidsmentioning
confidence: 99%
“…In addition, the diagnostic utility of CNAs has been shown in cattle and elk with bovine spongiform encephalopathy (Gordon et al, 2009). The analysis of cfDNA in domestic animals has been reported in several studies demonstrating cfDNA as useful markers in diagnosis (Beck et al, 2009(Beck et al, , 2013Brenig, Schütz & Urnovitz, 2002;Gordon et al, 2009;Mayer et al, 2013aMayer et al, , 2013bSchütz et al, 2005).…”
Section: Analysis Of Cell-free Circulating Nucleic Acidsmentioning
confidence: 99%
“…A recent study in dogs reported an increased level of cfDNA in neoplastic dogs compared to the ones without neoplasia, and among all the neoplastic cases, the concentration of cfDNA in the lymphoid neoplasia group was significantly higher [20]. In cattle, it was found that there were some different sequence tags in the serum between pregnant and non-pregnant dairy cows at different stages, and the distribution of cfDNA was significantly different [21]. Research about the diagnosis of bovine pregnancy showed that cfDNA could be used as a marker to detect early pregnancy in cattle [22].…”
Section: Discussionmentioning
confidence: 90%